Inhibitory Effect of the Biosynthesized ZnO Nanoparticles by Musa acuminata Fruits Peels against Pathogenic Bacteria Isolated from Diabetic Foot Ulcer - Ussama Asaed Fazel; Abbas Yaseen Hasan (ASJ - Academic Science Journal, 2024)
Zinc Oxide nanoparticles was synthesized by green method with zinc nitrate as precursor and alcoholic extract of Musa acuminata fruits peels as a reducing agent, color changing from white to yellowish -white, which was an indication of the formation of ZnO NPs. Characterization were made by UV-Visible light spectroscopy (Uv-Vis), X-Ray Diffraction (XRD), Atomic force microscopy (AFM) and Field Emission Scan Electron Microscope (FE-SEM), the results showed the sharp UV peaks were at 374 nm , XRD analysis estimated the crystallites sizes in 25.9 nm, AFM was used to determine the average size and forme of the nanoparticles which was 40, 45, and 50 nm, FE- SEM analysis displayed average particles size were 75.6 nm. Clinical of 125 samples were collected from diabetic foot ulcer from patients admitted to Baquba Teaching Hospital during beginning of November 2021 to the end of January 2022, included isolation and diagnosis of 76 isolates of Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and Staphylococcus epidermidis. Antibacterial activity test was done of ZnO NPs. which was tested toward these isolates. Different concentrations of ZnO NPs. (12.5, 25, 50, 100, 200) mg/ml were examined against pathogenic bacteria , the results showed the highest diameter of inhibition zone against E.coli, K.pneumoniae, P.aeruginosa, S.aureus and S.epidermidis were (28, 27, 31, 29. 26) mm respectively at concentration 200 mg/ ml and the lowest zone at concentration 12.5 mg/ml to the same isolates were (22, 23, 24, 24, 21) mm respectively.